2010
DOI: 10.1007/s00421-010-1564-x
|View full text |Cite
|
Sign up to set email alerts
|

Initial conditions influence the characteristics of ballistic contractions in the ankle dorsiflexors

Abstract: This study investigated the influence of different initial conditions on a subsequent fast (ballistic) isometric contraction of the ankle dorsiflexor muscles. Surface electromyograms (EMGs) of dorsiflexor and plantarflexor muscles were recorded during ballistic contractions performed without any pre-activation (BAL) and in ballistic contractions preceded by a sustained submaximal contraction (20% MVC) that was followed either by a rapid voluntary relaxation of the agonist muscle (VRBAL) or by a rapid antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 44 publications
1
8
4
Order By: Relevance
“…The current results may be construed as reflecting a type of preparatory inhibition in relation to elicited speech (Conrad, Benecke, and Goehmann, 1983;Richartz et al, 2010;Kolářová et al, 2016;Lebon et al, 2016;Doque et al, 2017). However, there is a difference in the time scales; in Lebon et al's study, inhibitory preparatory processes were found only 200 ms (but not 500 ms or 900 ms) prior to an imperative signal to move.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The current results may be construed as reflecting a type of preparatory inhibition in relation to elicited speech (Conrad, Benecke, and Goehmann, 1983;Richartz et al, 2010;Kolářová et al, 2016;Lebon et al, 2016;Doque et al, 2017). However, there is a difference in the time scales; in Lebon et al's study, inhibitory preparatory processes were found only 200 ms (but not 500 ms or 900 ms) prior to an imperative signal to move.…”
mentioning
confidence: 73%
“…Lip muscles activation, as recorded in sEMG, was higher during covert speech, compared to activation in a silent visualization task (Livesay et al, 1996). However, studies that have examined EMG muscle activity of peripheral musculature in tasks unrelated to language (Conrad, Benecke, and Goehmann, 1983;Richartz, Lévénez, Boucart, & Duchateau, 2010;Kolářová, Krobo, Kolář, Hluštík, & Polehlová, 2016), using both real and imagined movements, reported a 'premotor silent period' that is, an inhibition relative to baseline. Thus, the approach to data analysis in the current study was to compare the relative activation of articulatory muscles before (baseline) and during stimulus presentation (up to the 'go' cue for snetence repetition) in the different input and intended response conditions.…”
Section: Introductionmentioning
confidence: 98%
“…The lack of increase in sEMG magnitude, led the authors to suggest that the facilitated contractions may be due to musculoskeletal biomechanics: that is, during the flexion-to-extension sequence, the contracting flexors lengthen the extensors while coactive as antagonists, placing them at optimal muscle length immediately prior to their voluntary activation as an agonist (Gabriel et al, 2001a). Unfortunately, coactivation was not assessed as a probable mechanism in this particular study, but was later identified as a torque contributor by Richartz et al (2010). Richartz et al (2010) studied the maximal rate of isometric dorsiflexion torque development in response to the following conditions: (1) relaxation of the dorsiflexors; (2) pre-activation of the dorsiflexors at 20% MVC; and (3) a rapid reversal contraction of the plantar flexors at 25, 50, and 75% of MVC.…”
Section: Introductionmentioning
confidence: 86%
“…Unfortunately, coactivation was not assessed as a probable mechanism in this particular study, but was later identified as a torque contributor by Richartz et al (2010). Richartz et al (2010) studied the maximal rate of isometric dorsiflexion torque development in response to the following conditions: (1) relaxation of the dorsiflexors; (2) pre-activation of the dorsiflexors at 20% MVC; and (3) a rapid reversal contraction of the plantar flexors at 25, 50, and 75% of MVC. The average sEMG amplitude was calculated from its onset to 25 ms, 50 ms, and to the time point where dτ/dt max occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The breakpoint for this interrupted regression was calculated ( Linden, 2015 ) and the coefficients for the first part of linear regression, i.e., up to the breakpoint, was reported. To compare the absolute values of RFD between subjects, the peak force and the peak RFD were then normalized to the MVCF ( Richartz et al, 2010 ) obtained at PRE. Notably, the RFD data at POST were normalized with respect to the MVCF at PRE as well.…”
Section: Methodsmentioning
confidence: 99%